2011
DOI: 10.1038/oby.2010.292
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Activity After a Diet‐Induced Obesity

Abstract: Compared to lean subjects, obese men have less activation in the dorsolateral prefrontal cortex, a brain area implicated in the inhibition of inappropriate behavior, satiety, and meal termination. Whether this deficit precedes weight gain or is an acquired feature of obesity remains unknown. An adult animal model of obesity may provide insight to this question since brain imaging can be performed in lean vs. obese conditions in a controlled study. Seven diet‐induced obese adult minipigs were compared to nine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 32 publications
9
77
1
Order By: Relevance
“…Except for the obvious impact on health conditions, obese young adults face an increased risk of weight gain and cardiovascular disease later in life. 41,42 Along this line, accumulated obesity and interrupted physiological mechanisms might contribute to cognitive decline in the future. 43,44 In the present study, the central obese subjects revealed less brain activation due to the Stroop e®ect in the l-FPA, bilateral VLPFC and bilateral DLPFC compared to the non-central obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the obvious impact on health conditions, obese young adults face an increased risk of weight gain and cardiovascular disease later in life. 41,42 Along this line, accumulated obesity and interrupted physiological mechanisms might contribute to cognitive decline in the future. 43,44 In the present study, the central obese subjects revealed less brain activation due to the Stroop e®ect in the l-FPA, bilateral VLPFC and bilateral DLPFC compared to the non-central obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, some neurobiological studies used pigs to investigate human brain anomalies and feeding behaviour disorders (Sauleau et al, 2009). The changes in the metabolism of some brain structures in obese pigs, used as a model of obese humans, were studied using a SPECT imaging technique (Val-Laillet et al, 2011). This study suggests that, as in obese humans, compared with lean subjects, obese minipigs ( Figure 3) had relatively less activation in specific brain structures, including the prefrontal cortex, the nucleus accumbens and the ventral tegmental area.…”
Section: Neurobiological Similaritiesmentioning
confidence: 99%
“…Other studies could investigate interactions between nutrition and other functions such as reproduction, or to evaluate the putative sensorial effects induced by cognitive perturbations during prenatal, perinatal or childhood periods. For example, a recent brain imaging investigation using PET scan compared the cerebral blood flow of lean and obese minipigs (Val-Laillet et al 2011). …”
Section: Feeding Behaviormentioning
confidence: 99%